Legal Analysis of the Responsibility of Business Actors in Fulfilling Obligations for Halal Certification and BPOM Distribution Permits for Food Products - Yoel Latif; Nandang Sambas (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the legal liability of business actors in fulfilling the obligation of halal certification and distribution permits from the National Agency of Drug and Food Control (BPOM) for food products distributed in Indonesia. Halal certification and distribution permits are two essential instruments to ensure the safety, quality, and halal status of products in circulation. Using a normative juridical approach and literature study, this research examines the legal provisions regulating these obligations, including Law Number 33 of 2014 on Halal Product Assurance, Law Number 36 of 2009 on Health, and other implementing regulations. The results indicate that business actors bear both preventive and repressive responsibilities in ensuring that their products are safe and halal for consumption. Failure to fulfill these obligations may lead to administrative or criminal sanctions and negatively impact consumer rights. Therefore, active roles from the government and relevant institutions are necessary to promote awareness, supervision, and legal enforcement to increase business compliance with the applicable regulations.